1990
DOI: 10.1073/pnas.87.14.5383
|View full text |Cite
|
Sign up to set email alerts
|

Role for the Wilms tumor gene in genital development?

Abstract: Detailed molecular definition of the WAGR region at chromosome llpl3 has been achieved by chromosome breakpoint analysis and long-range restriction mapping. Here we describe the molecular detection of a cytogenetically invisible 1-megabase deletion in an individual with aniridia, cryptorchidism, and hypospadias but no Wilms tumor (WT). The region of overlap between this deletion and one associated with WT and similar genital anomalies but no aniridia covers a region of 350-400 kilobases, which is coincident wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0
1

Year Published

1992
1992
2002
2002

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(27 citation statements)
references
References 26 publications
(41 reference statements)
0
26
0
1
Order By: Relevance
“…In addition, genitourinary abnormalities such as cryptorchidism and hypospadias can be caused by the inactivation or deletion of one copy of the gene in germline DNA (8,11). A much more severe phenotype of nephropathy, intersex, and a high incidence of Wilms tumors are seen in patients with DenysDrash syndrome, which appears to be due to specific missense mutations within the zinc finger domain of the WTl protein (9).…”
mentioning
confidence: 99%
“…In addition, genitourinary abnormalities such as cryptorchidism and hypospadias can be caused by the inactivation or deletion of one copy of the gene in germline DNA (8,11). A much more severe phenotype of nephropathy, intersex, and a high incidence of Wilms tumors are seen in patients with DenysDrash syndrome, which appears to be due to specific missense mutations within the zinc finger domain of the WTl protein (9).…”
mentioning
confidence: 99%
“…Defects of the WT1 gene account for only a minority (<15%) of Wilms’ tumour (WT) cases [2], but have been demonstrated to cause the WAGR syndrome [3], Denys-Drash syndrome (DDS) [4]and Frasier syndrome (FS) [5]. The WAGR syndrome includes WT, aniridia, genital anomalies and mental retardation.…”
Section: Introductionmentioning
confidence: 99%
“…WAGR syndrome is caused by constitutional deletion of one copy of the WT1 gene [3]; DDS is caused by heterozygous (dominant negative) mutations of the same gene [4]and FS is determined by heterozygous mutations occurring at an alternative splice site at intron 9 between the regions encoding for the 3rd and 4th zinc finger motifs [9, 10]. …”
Section: Introductionmentioning
confidence: 99%
“…It was therefore hypothesized that at least some WTs arise due to the loss of function of both copies of a recessive tumor suppressor gene situated at 11p13 (4). Comprehensive mapping of the deletions present in WAGR patients confined the putative gene to a particular 325-kilobase (kb) Not I fragment (5)(6)(7) and indicated that this gene may also be involved with the genital anomalies seen in WAGR patients (8). Two groups (9,10) recently cloned a candidate WT gene from the 11p13 smallest region of overlap.…”
mentioning
confidence: 99%